AN ANALYSIS TEACHER’S MISTAKES IN TEACHING ENGLISH AT KINDERGARTEN AR-ROIHAN LAWANG - Tities Hijratur Rahmah; Melisa Wahyu Fandyasari (UIBU, 2020)
In Indonesia, English is taught even in the most basic educational institutions, that is Kindergarten. Based on informal interview with the teacher most of them do not graduate from English department, so the English they teach often contain the mistake. This study aimed to identify the mistakes that was made by the teacher during teaching and learning English. The design of this study is descriptive-qualitative research. The data of this study was collected from the sentences containing mistakes spoken by the teacher in teaching and learning activity at Kindergarten Ar-Roihan Lawang. The result of this study showed that the teacher did some mistakes when she taught English in the class. The researcher found 32 mistakes made by the teacher. The most mistakes made by the teacher is structure of the sentences with 18 mistakes, the second is the plural of nouns with 8 mistakes, and the last is tenses with 6 mistakes.